The archaeology of Islam - Insoll, Timothy, 1967- (Oxford, UK)
xiv, 274 sayfa
Keywords: “This book examines the archaeological implications of Islam as a force which can act upon all areas of life. Islam leaves distinctive material culture remains and distinctive categories of evidence which can be described, tested and used to indicate the presence of Muslim life in the archaeological record. The subject and the geographical area of Islam is vast. The author provides an assessment of the means and the methods of uncovering Islamic material records in the context of a wide range of times and places. Coverage extends from the origins of Islam in the seventh century AD up to the present.” --